Henri Lefebvre’s regressive-progressive method to understand the urban phenomenon of self-segregation in Cornélio Procópio, Brazil (Terr@ Plural, 2023)
From the second half of the twentieth century to today, the horizontal urban expansion of Cornélio Procópio has intensified in number of spatial forms, and the presence of open residential subdivisions, closed subdivisions and closed horizontal condominiums has been added to its spatial arrangement. The latter, the closed residential spaces, consist of the object of this study, whose scope is to understand them as a self-segregating spatial practice, as they are analyzed using Henri Lefebvre’s regressive-progressive method. Thus, in the method’s descriptive moment, it seeks to understand the phenomenon and its current configuration in the present, already in the analytical-regressive moment, investigating the genesis and development of the phenomenon in its different temporalities, and, finally, in the moment regressive-progressive, it is intended to analytically rediscover the phenomenon in the present, to understand its conflicts, contradictions and possibilities. The results reveal that such real estate incorporations are carried out, often irregularly, in order to meet the interests of this economic sector with the collusion of the State in total disregard for its segregationist socio-spatial consequences.
Keywords: horizontal urban sprawl; enclosed residential spaces; self-segregating spatial practice